PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA KEUANGAN PERUSAHAAN - Tasya Raphaela; Teodora Winda Mulia (Universitas Katolik Widya Mandala Surabaya, 2022)
The company’s financial statement contains the company’s financial information and how the company’s financial condition is. The company’s financial statements are needed by investors who will invest, academically as material for learning and one form of company transparency in managing its assets. Financial statement are not only influenced by assets, liabilities, and equity but also by intellectual capital used to manage and provide added value to the company’s financial performance. The purpose of this study is to empirically prove the effect of intellectual capital (MVAIC) on the company’s financial performance (ROA). This research is a type of quantitative research with multiple linear regression hypothesis testing. The type of data used is secondary in the form of company financial statements obtained from the official web of each company. The object of research used is a new listing companies on the Indonesia Stock Exchange for the period 2018-2020 and the sample obtained by the purposive sampling method. The independent variable in this study is intellectual capital which consists of value-added capital employed (VACA), value added human capital (VAHU), structural capital value added (STVA) dan relation capital efficiency (RCE) with the dependent variable financial performance (ROA). The result of the study using 118 samples of companies obtained the results that value added capital employed (VACA), structural capital value added (STVA) dan relation capital efficiency (RCE) had a positive effect on financial performance while value added human capital (VAHU) had a negative effect on company financial performance.